Intervensi Keperawatan Truncal Control Exercise terhadap Fungsi Ekstremitas Atas, Keseimbangan, dan Berjalan pada Klien Pascastroke - Kusnanto Kusnanto; Ganda Ardiansyah; Harmayetty Harmayetty (Universitas Airlangga, 2016)
Introduction: Poststroke clients will have impaired postural body that can have affect to their balance, ability to gait and function of the upper limb. Truncal control exercise can improve and maintain body postural be good. Rehabilitation poststroke still focusing on upper and lower limbs exercise of hemiplegia compared postural body’s repair.Methods: This type of research used experimental with quasy control group pretest – postest design. The number of samples obtained with consecutive sampling techniques that appropriate criteria research consists of 20 respondents (n = 10 treatment-and n-control = 10). The independent variable is the truncal control exercise. The dependent variable is the function of the upper limb, balance, and gait. Data were collected by using observation and checklist sheets. Data were analyzed using independent t-test and paired t-test with α = 0,05.Results: The results of statistical tests performed in the treatment group and the control was obtained p-value of the functional capabilities of the upper limb = 0.270 and p-value of performance of upper limb function = 0.289. The results of statistical tests performed in the treatment group and the control was obtained p-value of balance = 0.017. The results of statistical tests performed in the treatment group and the control was obtained p-value of gait = 0.026.Discussion: Nursing interventions truncal control exercise have less effective results to changes in upper limb function, but it is effective to balance and walk clients pascastroke. Nursing interventions truncal control exercise can be continued as a form of collaborative action for medical-surgical nurse with physiotherapy to optimize rehabilitation programs of posstroke clients with balance and gait problems in clinic or home’s client.